2017
DOI: 10.24017/science.2017.3.33
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Pavement Evaluation: A Case Study

Abstract: This study is a survey to evaluate the flexible pavement conditions to determine and specify the types of the failures in the pavement for the selected highway. It is very significant to evaluate and identify the causes of the flexible pavement failures and select the proper and best treatment and maintenance type. The study had two major and critical goals which covered by considering the following three tasks; the first was the visual evaluation and inspection of existing flexible pavement conditions includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…e model factors and their interactions were assigned negative and positive signs to indicate the antagonistic or synergistic effects of the variables on the performance of asphalt mixes. e models for the axial strain, TSR, and stability of asphalt mixtures comprising all the terms are shown in equations ( 8)- (10)…”
Section: Historical Data Designmentioning
confidence: 99%
See 1 more Smart Citation
“…e model factors and their interactions were assigned negative and positive signs to indicate the antagonistic or synergistic effects of the variables on the performance of asphalt mixes. e models for the axial strain, TSR, and stability of asphalt mixtures comprising all the terms are shown in equations ( 8)- (10)…”
Section: Historical Data Designmentioning
confidence: 99%
“…Al-Arkawazi conducted a survey to determine the type of flexible pavement failures for the selected Khanaqin-Kalar Highway, Iraq. According to his study, assessments showed that most failures in the pavement were serious and extreme surface deformation [10]. Moreover, Hosseini et al developed a framework for connecting quality during asphalt mix production and surface construction to in-service performance through statistical correlation at the network level [11].…”
Section: Introductionmentioning
confidence: 99%
“…The current PSI for a given section of flexible highway can be calculated from the average slope variance, average rut depth, and cracking and patching, in accordance with AASHO Road Test Report 5 [20]. The equation can be written as shown in (1).…”
Section: F Present Serviceability Index Calculationmentioning
confidence: 99%
“…HE transportation system occupies a special part in the economic growth of any state. Safe, comfortable, and fast transportation systems allow people to connect safely and fast, and ease goods distribution in the country [1].…”
Section: Introductionmentioning
confidence: 99%
“…A conventional flexible pavement is constructed using bituminous materials and granular materials on top of the subgrade layer. Generally, there are four types of failures would happen within the flexible pavement: the surface deformation, the cracking, the disintegration and surface defects(Arkawazi, 2017), where surface rutting or the permanent deformation and the fatigue cracking are the two principal structural failures. The weak subgrade and base course layer are usually the cause of the surface rutting when the accumulated load is applied.…”
mentioning
confidence: 99%